Redesign of the User Interface of the School Examination Website of SMK Nusa Dua Using the Design Sprint Method - Giri Wijaya, Gede Wesbyana; A.A. Istri Ita Paramitha; Eka Grana Aristyana Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The Online Exam Website has encountered issues related to its user interface and lack of mobile responsiveness. This study aims to analyze and enhance the User Interface (UI) design and improve the User Experience (UX) to better meet current user needs. The research employed a mixed-methods approach, collecting qualitative data through interviews and observations, and quantitative data through a questionnaire based on the System Usability Scale (SUS). Subjects were selected using the Focus Group Discussion (FGD) technique, involving 6–10 active users. The study applied the Design Sprint method, focusing on a human-centered approach to develop solutions based on user needs. Data were analyzed using descriptive qualitative and quantitative techniques. The findings indicate a significant improvement in UI and UX aspects based on user feedback on the newly developed prototype. The results imply that the application of the Design Sprint method is effective in optimizing website design according to actual user requirements.